Chromatic Number and some Properties of Pseudo-Von Neumann Regular graph of Cartesian Product of Rings - Nermen J. Khalel; Nabeel E. Arif (Tikrit Journal of Pure Science)
Let R be a commutative ring, the Pseudo – Von Neumann  regular graph of the ring R is define as a graph whose vertex set consists of all elements of R and any two distinct vertices a and b are adjacent if and only if , this graph is denoted by P-VG(R), in this work we got some new results about chromatic number of Pseudo-Von Neumann regular graph of cartesian product of rings.